Pelaksanaan Metode Show and Tell Dalam Keterampilan Berbicara Siswa Kelas III di Sekolah Dasar - Sari, Dini Puspita; Latif, Latif (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Speaking skills are fundamental abilities that need to be developed from the elementary school level because they are closely related to students’ communication abilities and self-confidence; however, speaking instruction in schools still tends to be teacher-centered. This study aims to describe the implementation of the Show and Tell method in improving the speaking skills of third-grade students at SDN 21 Pekanbaru. The research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. The research instruments included interview sheets, observation sheets, and documentation review sheets. The findings show that the teacher understands and routinely applies the Show and Tell method by utilizing simple media that are closely related to students’ daily experiences. This method was proven to enhance students’ speaking confidence, fluency, pronunciation, and ability to construct coherent utterances. The main challenges involved differences in students’ self-confidence levels and limited instructional time, but these were addressed through motivation, guidance, and structured turn-taking. Overall, the Show and Tell method effectively supports the development of students’ speaking skills while fostering their self-confidence and positive communication abilities in elementary school learning.